Examination of drinking motives during the pandemic: mediating effects of drinking motives in the relationship between impulsivity and alcohol use. Issue 2 (31st August 2022) - Dinc, Linda; Marzetti, Jemma
Abstract : Purpose: Previous research have shown that individuals with high trait impulsivity are at high risk of engaging in problem alcohol use and that drinking motives differentially predicted alcohol use and problems. This study aimed to investigate whether these previously shown associations still existed during the global outbreak of the pandemic, COVID-19, which resulted in a long period of lockdown and raised concerns about the effects of alcohol. Design/methodology/approach: The data was collected from 185 adults between ages of 18 and 35 during the lockdown period (November 20–May 21) through an online survey. Participants completed an impulsivity questionnaire, drinking motives and alcohol use measures. Findings: The results revealed that enhancement and coping motives mediated the effects of positive and negative urgency, respectively, and lack of premeditation facet of impulsivity was directly linked to alcohol use. These findings are partially in line with the previous studies before the lockdown. Research limitations/implications: Overall, individuals with particularly high urgency and premeditation maybe at high risk for problem alcohol use and may require tailored support for regulating emotions, particularly during stressful life events such as a global pandemic. Practical implications: Findings may inform prevention and intervention strategies. Individuals with high trait urgency may benefit from more adaptive coping strategies such as learning specific emotion regulation strategies to minimise engaging in risk behaviours in stressful situations. Originality/value: Findings suggest that traits positive and negative urgency are risk factors for alcohol use through enhancement and coping motives respectively, and these associations are particularly strong during stressful life events.